Factors associated with elevated serum chromogranin A levels in patients with autoimmune gastritis - Kalkan, Çağdaş; Karakaya, Fatih; Soykan, İrfan (Turkish Journal of Gastroenterology, 2016)
Abstract Background/Aims: Chromogranin A is an important tool in the diagnosis of neuroendocrine tumors. Autoimmune gastritis is an autoimmune disorder marked by hypergastrinemia, which stimulates enterochromaffin-like cell proliferation. Chromogranin A is also elevated in autoimmune gastritis patients with a different level of increase in each patient. The goal of this study is to explore constituents that influence serum chromogranin A levels in autoimmune gastritis patients. Materials and Methods: One hundred and eighty-eight autoimmune gastritis patients and 20 patients with type I gastric carcinoid tumors were analyzed retrospectively and compared to 110 functional dyspepsia patients in terms of factors that might affect serum chromogranin A levels. Results: The mean serum chromogranin A level was 171.17±67.3 ng/mL in autoimmune gastritis patients (n=62) without enterochromaffin-like cell hyperplasia, and 303.3±102.82 ng/mL in patients (n=126) with enterochromaffin-like cell hyperplasia (p<0.001). The presence of corpus atrophy (p=0.026, OR: 5.03, CI 95%: 1.21–20.88, β=1.61) and presence of enterochromaffin-like cell hyperplasia (p=0.017, OR: 6.59, CI 95%: 1.4–31.08, β=1.88) were found as risk factors associated with serum chromogranin A level. Conclusion: Factors influencing raised serum chromogranin A levels in autoimmune gastritis were the presence of ECL cell hyperplasia and serum gastrin levels. Serum chromogranin A levels maybe helpful in distinguishing autoimmune gastritis patients and gastric carcinoid type I from the control group, but not useful in the differentiation of individuals with autoimmune gastritis from patients with gastric carcinoids.